2020
DOI: 10.1055/s-0040-1709986
|View full text |Cite
|
Sign up to set email alerts
|

Proptosis in Otorhinolaryngology: An Overview

Abstract: Introduction Ear, nose and throat (ENT)pathologies can present with proptosis as the early manifestation. The majority of ENT pathologies present with ocular manifestations, due to close anatomical relationship. Objective To study proptosis in ENT disorders in terms of etiology, pathogenesis, and management. Methods The present article is a prospective study conducted at a tertiary care center, in Telangana, India. Patients presenting with proptosis secondary to ENT disorders were thoroughl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…All patients underwent endoscopic otolaryngological examination and tone аudiometry, the results of ophthalmological and neurological examinations were studied [8]. In addition, the following laboratory examinations were performed: general and biochemical blood tests, coagulation test, determination of D-dimer parameters, and cerebrospinal fluid (CSF) analysis [5,9]. Neuroimaging methods included magnetic resonance imaging (MRI) and computed tomography (CT) with contrast medium.…”
Section: Materials and Methods Of Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…All patients underwent endoscopic otolaryngological examination and tone аudiometry, the results of ophthalmological and neurological examinations were studied [8]. In addition, the following laboratory examinations were performed: general and biochemical blood tests, coagulation test, determination of D-dimer parameters, and cerebrospinal fluid (CSF) analysis [5,9]. Neuroimaging methods included magnetic resonance imaging (MRI) and computed tomography (CT) with contrast medium.…”
Section: Materials and Methods Of Researchmentioning
confidence: 99%
“…CVT in patients was determined by the presence of some prevailing syndromes: isolated intracranial hypertension (headache), focal neurological deficit syndrome, ophthalmological syndrome, neuroimaging data [4,9].…”
Section: Materials and Methods Of Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…18 A study which conducted detailed assessment of 53 patients who had proptosis, reported the most common aetiology found was neoplastic (60%) of which sinonasal squamous cell carcinoma followed by juvenile nasopharyngeal angiofibroma were the most common causes 14 with similar findings reported from another study in the same region as well. 19 In a prospective study commonest cause of proptosis was malignancy of nose and paranasal sinuses (27.3%) of which squamous cell carcinoma was common. Frontoethmoid mucocele (22.7%) was the second common cause followed by fungal sinusitis.…”
Section: Per-centagementioning
confidence: 99%